Changing Functionality of Surfaces by Directed Self-Assembly Using Oligonucleotides—The Oligo-Tag - Frank F. Bier; Frank Kleinjung; Eva Ehrentreich-Förster; Frieder W. Scheller (BioTechniques, 1999)
A method is presented to modify surfaces for biotechnological applications. Oligonucleotides have been coupled covalently to a pre-activated surface. Complementary oligonucleotides hybridize to the surface, which are conjugated with functionalities. The oligonucleotides serve as “Oligo-Tags” for these functionalities that now are linked specifically and reversibly. The approach might be used to change DNA-arrays into arrays of arbitrary ligands. We demonstrate the method with an optical wave guide grating coupler as a sensing surface using two different haptens as examples for a variety of functionalities. The haptens were 2,4-dichlorophenoxyacetic acid and atrazin and are recognized by specific antibodies. The surface created was completely regenerable by alkaline washing or temperature increase without any loss of binding capacity. Specificity was demonstrated by competitive binding of antibody in presence and absence of analyte; unspecific binding has not been observed.